O poema e os germes de tudo - Fiorussi, André (Texto Poético, 2019)
Livro resenhado: AQUEIVA, Marco. Germes entre dias brancos. São Paulo: Patuá, 2016. — DOI: http://dx.doi.org/10.25094/rtp.2019n27a572